Information systems in the big data era : CAiSE Forum 2018, Tallinn, Estonia, June 11-15, 2018, Proceedings /: CAiSE Forum 2018, Tallinn, Estonia, June 11-15, 2018, Proceedings. (2018) - Unknown
No abstract available